Charting Extracellular Transcriptomes in The Human Biofluid RNA Atlas - Hulstaert, Eva; Morlion, Annelien; Avila Cobos, Francisco; Verniers, Kimberly; Nuytens, Justine; Vanden Eynde, Eveline; Yigit, Nurten; Anckaert, Jasper; Geerts, Anja; Hindryckx, Pieter; Jacques, Peggy; Brusselle, Guy; et al. (Cell reports (Cambridge), 2020)
Extracellular RNAs present in biofluids have emerged as potential biomarkers for disease. Where most studies focus on blood-derived fluids, other biofluids may be more informative. We present an atlas of messenger, circular, and small RNA transcriptomes of a comprehensive collection of 20 human biofluids. By means of synthetic spike-in controls, we compare RNA content across biofluids, revealing a 10,000-fold difference in concentration. The circular RNA fraction is increased in most biofluids compared to tissues. Each biofluid transcriptome is enriched for RNA molecules derived from specific tissues and cell types. Our atlas enables an informed selection of the most relevant biofluid to monitor particular diseases. To verify the biomarker potential in these biofluids, four validation cohorts representing a broad spectrum of diseases were profiled, revealing numerous differential RNAs between case and control subjects. Spike-normalized data are publicly available in the R2 web portal for further exploration. [Display omitted] •Messenger, circular, and small RNA transcriptomes of 20 biofluids are studied•Synthetic spike-in controls allow direct comparison between biofluids•Tissues of origin are assessed per biofluid•The results can guide the selection of biofluids in biomarker research Hulstaert et al. present an atlas of messenger, circular, and small RNA transcriptomes of 20 biofluids. Spike-in RNA controls allow direct comparison of the RNA content between the biofluids. Tissues of origin are assessed per biofluid and can guide the selection of the most appropriate biofluid for future biomarker studies.